A study of the Quantitative Criteria in Chinese Proficiency Grading Standards for International Chinese Language Education through the Four-dimension benchmarks - Amkid, Supidchaya (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
The objective of this research was to study the relationship between quantitative criteria. The quantitative criteria consist of a syllable, a Chinese character, a vocabulary, and grammar through the Four-dimension benchmarks. The sample groups used in this study were the standard GF0025-2021 and the book series 《国际中文教育中文水平等级标准》(国际标准·应用解读本). The result revealed that a syllable, Chinese character, vocabulary, and grammar are interrelated in sequence. A syllable, Chinese character, vocabulary reflect a clear three-dimensionality. Chinese characters play a role in helping to understand syllables better, and vocabulary plays a role in helping to understand a syllable and Chinese character better. When these three dimensions are taken into account in conjunction with grammar, it is found that the reader requires a deeper understanding. In addition, some observations were found in explaining grammar. Therefore, the researcher proposes additional amendments to make the content complete and suitable for teaching Chinese to foreign learners more appropriately.